Respuesta :

Answer:

[tex]y=-(1/2)(x+3)^{2} -1[/tex]

Step-by-step explanation:

we know that

The equation of a vertical parabola in vertex form is equal to

[tex]y=a(x-h)^{2} +k[/tex]

where

(h,k) is the vertex of the parabola

In this problem the vertex is the point [tex](-3,-1)[/tex]

substitute

[tex]y=a(x+3)^{2} -1[/tex]

Observing the problem we have two cases that have the same vertex

case A) [tex]y=-(1/2)(x+3)^{2} -1[/tex]

case B) [tex]y=-(5/8)(x+3)^{2} -1[/tex]

Verify each case with the point [tex](1,-9)[/tex]

substitute the value of x and the value of y in the equation and then compare the result

case A) [tex]-9=-(1/2)(1+3)^{2} -1[/tex]

[tex]-9=-9[/tex] -----> is true

case B) [tex]-9=-(5/8)(1+3)^{2} -1[/tex]

[tex]-9=-11[/tex] ------> is not true

therefore

the function is [tex]y=-(1/2)(x+3)^{2} -1[/tex]

ACCESS MORE